(untitled) (KASBIT Business Journal, 2026)
Abstract Purpose – the purpose of the paper is to check the impact of digital financial literacy on financial wellbeing the mediating role of digital financial inclusion. Design/Methodology/Approach – to fulfil the requirements of the study online survey was conducted and data were collected from 323 individuals by using Convenience sampling technique. The time span of data collection were the month of January-May 2024. Simple linear regression model were utilized by using SPSS & PROCESS macro by Andrew F. Hayes used of mediation analysis. Findings – the results of the study reveals that a strong moderate positive correlation between DFL and FW. The study demonstrates a partial mediation effect of DFI on the relationship between DFL and FWB, indicating that while DFI plays a significant role, DFL also directly influences FWB. According to the study, digital financial literacy has a beneficial influence on financial wellbeing by considerably enhancing DFI (digital financial inclusion, β = 0.726, p < 0.001). Research limitations/ Implications – the first about generalizability, means findings might only be relevant to Pakistan’s particular population of internet users. Second, overall reliability and validity of the study’s may be impacted by limitations in the quality of the data, possible biases in participant replies, and the availability of reliable financial behaviour data. There might be restrictions relating to one’s own reporting biases and the digital literacy of the participants because the data was gathered via a web-based questionnaire. Originality/value - The study makes contribution in the field of digital finance, along with this investigation insights an important perspective for financial institutions, investors, government and substantial implications for policymakers and educational entities. These findings can inform and guide their endeavours to advance financial literacy, foster financial inclusion, and enhance the financial wellbeing.